2007
DOI: 10.1111/j.1572-0241.2007.01065.x
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Habit and Load Influence Age at Diagnosis and Disease Extent in Ulcerative Colitis

Abstract: Smoking habit influences the age at diagnosis and changes in disease extent in UC. Mechanisms are likely to be complex and require further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
5
5

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 51 publications
5
55
5
5
Order By: Relevance
“…Odes et al 35 also reported active smoking's protective effect against surgery in patients with UC. Aldhous et al, 4 however, observed no difference in time from diagnosis of UC to colectomy in those patients requiring surgery, between current smokers and nonsmokers; however, found that ex-smokers demonstrated a shorter time period between diagnosis and colectomy than nonsmokers. Boyko et al 34 found that exsmokers more frequently underwent colectomy than current smokers or nonsmokers; however no such difference was observed between current smoker and nonsmoker groups.…”
Section: 21mentioning
confidence: 95%
See 4 more Smart Citations
“…Odes et al 35 also reported active smoking's protective effect against surgery in patients with UC. Aldhous et al, 4 however, observed no difference in time from diagnosis of UC to colectomy in those patients requiring surgery, between current smokers and nonsmokers; however, found that ex-smokers demonstrated a shorter time period between diagnosis and colectomy than nonsmokers. Boyko et al 34 found that exsmokers more frequently underwent colectomy than current smokers or nonsmokers; however no such difference was observed between current smoker and nonsmoker groups.…”
Section: 21mentioning
confidence: 95%
“…1,4,5,10,16,24 That is to say, heavier smokers are less likely to develop UC than lighter smokers 4 and current smokers who have a diagnosis of UC are more likely to have milder disease than ex-smokers and nonsmokers with UC. 1,4,5,24 Indeed, relatively heavy smokers have been observed to have less macroscopic and histological evidence of disease on colonoscopic examination, as compared with lighter smokers, ex-smokers and nonsmokers with UC. 4 Intermittent smokers have often been reported to experience symptomatic exacerbation during periods of nonsmoking and alleviation of symptoms on recommencement of smoking.…”
Section: 21mentioning
confidence: 99%
See 3 more Smart Citations